Overlooked monkeypox cases among men having sex with men during the 2022 outbreak – a retrospective study. (March 2023) - Wieder-Feinsod, Anat; Zilberman, Tal; Erster, Oran; Kolasko, Gal Wagner; Biber, Asaf; Gophen, Ruth; Hoffman, Tomer; Litchevsky, Vladislav; Olmer, Liraz; Yahav, Dafna; Levy, Itzchak
Highlights: In the current outbreak, monkeypox might get easily overlooked outside of endemic areas. Monkeypox might be misdiagnosed as other sexually transmitted diseases. Misdiagnosis leads to delayed isolation and administration of inappropriate treatment. Abstract: Objectives: The aim of this study was to characterize overlooked cases of patients with monkeypox infection in the 2022 outbreak. Methods: Clinical characteristics of 26 patients who were misdiagnosed with other diseases were described. Results: Of the 26 patients who were misdiagnosed, six (23%) were given a diagnosis of bacterial tonsillitis, six (23%) were diagnosed with primary syphilis, five (19.2%) with oral or genital herpes, and four (15.3%) with bacterial proctitis or anal abscess. The average time interval between missed and right diagnosis was 4.4 days. There was no difference in the missed cases between the early and the later month of the outbreak. Conclusion: Monkeypox might still be commonly overlooked, especially in patients presenting with fever and sore throat or solitary ulcer as sole manifestations.